Legal Protection of Customers from Data Theft Through Skimming - Ketut Sudiarsa; Anak Agung Ayu Ngurah Sri Rahayu Gorda; I Gede Agus Kurniawan (Faculty of Law, Universitas Pekalongan, 2025)
Theft of bank customer money through ATM card duplication (skimming) is one of the banking crimes. This paper is the result of research focusing on the study of legal protection for bank customers due to skimming crimes. This research was conducted with a normative legal approach using a data collection method through a literature study conducted on secondary data. Furthermore, the data analysis method uses analytical descriptive analysis. Meanwhile, the urgency of this research is expected to be a source of reference for banking institutions to make legal protection efforts as well as for law enforcement officers in making efforts to overcome skimming crimes as a concrete form of legal protection for bank customers who are harmed by skimming crimes. Based on the analysis, it was identified that the crime of breaking into customer money using the skimming method is one of the high-tech (cybercrime) crimes in the banking sector. The act is included in the criminal act of information and electronic transactions which prohibits any person intentionally and without rights or against the law from accessing computers and/or electronic systems in any way with the aim of obtaining electronic information and/or electronic documents as regulated in Article 30 paragraph (2) of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions (ITE Law). Protection for customers who are victims of skimming crimes can be carried out in the context of criminal law enforcement and civil law enforcement.